Relaxation of defect structure in ultrasonic wave field and acoustic emission in LiF single crystals - Kravtsov, M.V.; Lyashenko, O.V.; Onanko, A.P. (Functional Materials, 2004)
Correlation of dependences of acoustic emission parameters and the combination aggregate harmonic amplitude has been studied for two colliding large-amplitude ultrasonic waves in LiF single crystals. This correlation is related to the defect structure relaxation in ultrasonic wave field.